Proceedings of the 5th International Conference on Food, Agriculture and Natural Resources (FANRes 2019) 2020
DOI: 10.2991/aer.k.200325.075
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Mycoflora from Mace and Seed of Nutmeg (Myristica fragrans Houtt) as a Source of Antifungal Compounds

Abstract: The nutmeg extract had been recognized as the source of antioxidant and antimicrobial activity. The aims of this study were to obtain endophytic fungi isolated from the mace and seed of Nutmeg (Myristica fragrans Houtt) and to determine antifungal activity of those isolates. Microbiol routine assay were conducted and it consists of three stages, namely isolation of endophytic fungi, identification of fungus and antifungal activity test by using dual culture. Sixteen endophytic fungus isolates were found in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Indonesia is the world's leading producer of nutmeg [4,5]. Many studies on the bioactive properties of nutmeg have indicated that it has anti-diabetic, antibacterial, antifungal, anticonvulsant, anti-inflammatory, antioxidant, anticancer, and other benefits [6][7][8][9]. However, rapid population growth, industrialization, global IOP Publishing doi:10.1088/1755-1315/1271/1/012063 2 climate change, and exploiting and utilizing medicinal plants have mainly contributed to their extinction [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indonesia is the world's leading producer of nutmeg [4,5]. Many studies on the bioactive properties of nutmeg have indicated that it has anti-diabetic, antibacterial, antifungal, anticonvulsant, anti-inflammatory, antioxidant, anticancer, and other benefits [6][7][8][9]. However, rapid population growth, industrialization, global IOP Publishing doi:10.1088/1755-1315/1271/1/012063 2 climate change, and exploiting and utilizing medicinal plants have mainly contributed to their extinction [10].…”
Section: Introductionmentioning
confidence: 99%
“…One approach that has been developed is to use endophytic fungi to produce bioactive components similar to those found in the host plant [11] Nearly 200 isolates of endophytic fungi were obtained from the pericarp, leaf, and nutmeg seeds of Bogor, West Java, Indonesia [12]. Endophytic fungi isolated from nutmeg mace and seeds have antifungal activity [6]. The medium used to grow endophytes impacts secondary metabolite production and biological activity [13].…”
Section: Introductionmentioning
confidence: 99%